A Neglected Semi-Stylized Fact of Daily Stock Returns - Laurie Davies; Walter Krämer (Center for Economic Studies and ifo Institute (CESifo), 2016)
We plot aggregated daily stock returns with absolute value less than x against x and show empirically that this produces a typical spoon-shaped pattern which indicates a special type of asymmetry which has not been discussed before. This pattern disappears when individual returns are averaged; it is also absent in stock price indices, which points to explanations based on firm-specific drivers of returns.
Keywords: C58; G10; G15; 330; financial economics; empirical finance; stylized facts; stock returns; spoon effect